EFFECT OF SAWDUST AS PARTIAL REPLACEMENT OF SAND IN CONCRETE - MUHEDIN, DABAN A.; QADIR, SANGAR J.; HAMAKAREEM, MADEH I.; RASH, AHMED J. HAMA (Journal of Duhok University, 2021)
In the past, river sand was main choice for fine aggregate but due to nonscientific methods for excavation from river beds it has been depleted and leads to environmental concern. Most of the waste sawdust are being dumped into landfill areas which is undesirable because it has a negative impact on environment. This research investigated the effects of sawdust as partial replacement for fine aggregate in concrete structures. Compressive, tensile and flexural strength were investigated and evaluated at 7, 14 and 28 days. In this study four concrete mixes were prepared, first one was control mix and in other three mixes sand was replaced by the following percentages 5%, 10% and 15%. Results shows that by increasing the amount of sawdust in concrete samples; compressive, tensile and flexural strength will reduce. Compressive strength for 5% of sawdust replacement at 28 days was 26.2 MPa, while for 10% was 20.1 MPa and for 15% was 15.9 MPa. The test results, indicated that 5% of sawdust can be used in concrete structures.